Some reflections on the role of the eco-schools program in the promotion of sustainable HEIs: A case study in Portugal - Sara Sousa (Administrative Sciences, 2022)
Currently, the Eco-Schools program plays a key role in the application of the concepts of environmental education and management in the daily life of schools. This program is considered the largest environmental education program for schools of different levels in the world and continues to grow with the constant and ambitious mission to improve literacy and change environmental behaviors, particularly among the youngest who are now students, but will be the future decision-makers, politicians, managers, teachers, and parents. Thus, it is essential to involve this younger generation in the construction not only of a school, but also of a more sustainable community. This research study presents a set of reflections on the main guidelines of the Eco-Schools program, focusing on its methodology and areas of activity. It also analyzes the reality in Portugal, a country where the Eco-Schools program has been developed since 1996 by the European Blue Flag Association (ABAE), an association that works in the three components of sustainability (environmental, economic, and social), reinforcing the importance of educating and involving all the individuals of the community in joint actions for a more sustainable society. The case study consists of a Portuguese Higher Education Institution (HEI) awarded the Green Flag since the year it enrolled in the program, 2018/19. A description, analysis, and reflections are made on some of the main measures implemented in the last academic year within the scope of the Eco-Schools program, noting that, despite some implementation difficulties, the program was successfully developed, involving the participation of students, teachers, staff, and outside school community members, thus contributing to a more sustainable society.
Keywords: 350; eco-schools program; environmental protection; higher education institutions; Portugal; sustainability